A research on Sri America's efforts to sustain its survival in a fast expanding travel industry in Kuala Lumpur / Noriah Din ... [et al.] - Din, Noriah; Baharum, Ailida; Ahmad Noordin, Naida; Mohd Thani, Mohd Fuad; Idris, Johari (1985)
The main objective of this research is to find out in detail the activities carried out by Sri America and how these activities and programme are geared into achieving the company objective and whether they would be succesful.